Evaluación del efecto de algunas características inherentes al animal sobre la terneza de la carne bovina (2015)
I evaluated the diﬀerence of the tenderness between bovine meats in diﬀerent ages within the normal ranks to which these animals are taken to sacriﬁce, being calculated its indices of greasy deposition according to sex due to the diﬀerences of this characteristic found between males and females, similarly with bullﬁghting and indicus races. In order to determine the fat concentration in each one of the samples and evaluation of tenderness a Warner Bratzler texturometer was used. The collected data were analyzed through a multiple linear regression model. The analysis of the results indicates that in the bovine cattle, the diﬀerences of terneza by increase of fat deposition are also are carried out to superior ages, although the relation is inverse. The percentage of fat including within each muscular piece is directly related to greater tenderness. Minors sacriﬁce ages produce minors resistance to the cut.